Perceptions of different stakeholders on managing collaborative university-industry R&D funded contracts - Fernandes, Aldora Gabriela Gomes (2016)
A new program and project management (PgPM) approach especially devoted to support collaborative university-industry R&D funded contracts is being developed from an exploratory study. This paper describes how the identified key program management activities/practices are dependent on the program stakeholders' characteristics, namely contractual relationship - university vs. industry, professional category, role in the program context, PM experience, level of education, gender and age. A sample of 170 questionnaire responses from stakeholders of a real program, named HMIExcel, is used. There were few different perceptions observed between program stakeholders, which might indicate that the key program management activities within the PgPM approach are so relevant that there is a general consensus between different stakeholders.